(untitled) (Research, Society and Development, 2021)
The Brazil and Mexico started their International Public Sector Accounting Standards (IPSAS) IPSAS adoption strategies in 2008 and consider the importance of the accountant role in this process and the existence of specific undergraduate Accounting programmes in the two countries. This study aims to compare the offer of courses about public sector accounting in public institutions of higher education in these countries during year 2018 & 2019, under Institutional Theory perspective. The methodology of this article consists of a documentary analysis of the curricula in force of website of the Public Institutions of Higher Education (PIHE) of each federative entity of Brazil and Mexico. The results show great diversity in the offer of disciplines among the 76 Brazilian and in the 39 Mexican institutions, with an average of only 3 and 1,3 courses by each country respectively. In Brazil, every institution has at least one mandatory Public Sector Accounting discipline, whilst only 28 Mexican institutions offer as obligatory. If institutional legitimacy consider education in Mexican and Brazilian IPSAS adoption strategies, the diffusion of IPSAS accrual accounting information will account for a huge network of more than 1000 of people involved. Furthermore, it highlights the weakness of the public sector approach to develop professional skills (normative isomorphism) in line with emerging trends in Public Sector Accounting for transparency. This article contributes to show what has been considered from the perspective of higher education of future public sector accounting professionals aligned with the IPSAS adoption strategies that involve Brazil and Mexico.